2013
DOI: 10.1007/s12265-013-9508-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of Inflammation and Its Mediators in Acute Ischemic Stroke

Abstract: Inflammation plays an important role in the pathogenesis of ischemic stroke and other forms of ischemic brain injury. Increasing evidence suggests that inflammatory response is a double-edged sword, as it not only exacerbates secondary brain injury in the acute stage of stroke but also beneficially contributes to brain recovery after stroke. In this article, we provide an overview on the role of inflammation and its mediators in acute ischemic stroke. We discuss various pro-inflammatory and anti-inflammatory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
285
2
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(303 citation statements)
references
References 198 publications
(211 reference statements)
10
285
2
6
Order By: Relevance
“…However, a growing body of evidence indicates the importance of immune-mediated responses for central nervous system (CNS) injury repair and recovery [7], revealing the controversial complexity of inflammatory responses in ischemic stroke. Besides microglia, a host of immune cells, including neutrophils, monocytes/macrophages, natural killer cells, and lymphocytes, infiltrate into the stroked hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…However, a growing body of evidence indicates the importance of immune-mediated responses for central nervous system (CNS) injury repair and recovery [7], revealing the controversial complexity of inflammatory responses in ischemic stroke. Besides microglia, a host of immune cells, including neutrophils, monocytes/macrophages, natural killer cells, and lymphocytes, infiltrate into the stroked hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is a basic reaction to irritation, infection or other injury 11 . It is an essential step in the mechanisms of ischemic stroke and other forms of ischemic brain injury 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies suggested that systemic inflammation could influence the susceptibility of patients to stroke and subsequent prognosis 12,13 . Therefore test of the anti-inflammatory and antinociceptive effect of the essential oil recipe named OR consisting of white pepper, long pepper, cinnamon, saffron and myrrh may help us to understand the traditional theory.…”
Section: Introductionmentioning
confidence: 99%
“…After an ischemic insult, several key transcriptional factors, such as hypoxia inducible factor 1 (HIF-1), nuclear factor-κB (NF-κB), interferon regulatory factor 1 (IRF1), and STAT3, are up-regulated via calcium-induced signaling pathways, increased oxygen free radicals, and hypoxia (30)(31)(32). These transcriptional factors induce the expression of numerous pro-inflammatory genes, including tumor necrosis factor α (TNFα), interleukin 1α (IL-1α) and 1β (IL-1β), intercellular adhesion molecule 1 (ICAM-1), and selectins (11,30,33). Circulating leukocytes interact with these adhesion molecules to adhere to brain endothelium, transmigrate through the vascular wall, and enter the brain parenchyma.…”
Section: Inflammation After Strokementioning
confidence: 99%